Agricultural insurance for development: Past, present, and future - Robles, Miguel (International Food Policy Research Institute, 2021)
Agricultural production is a risky activity subject to several contingencies that make farming incomes unstable and unpredictable from year to year. Bakst, Sewell, and Wright (2016) report that the Economic Research Service of the US Department of Agriculture (USDA) identifies five types of farming risk: (1) human and personal risk (such as human health), (2) institutional risk (regarding governmental action), (3) financial risk (such as access to capital), (4) price or market risk, and (5) production risk (such as weather and pests). The HIV/AIDS pandemic in African countries in the early 2000s is an example of a human risk that affected agricultural output and labor supply and demand. Land expropriation, land reforms, and unanticipated changes in the agricultural tax system are examples of institutional risk that can depress investment in the agricultural sector. Nonavailability of funds in the formal or informal financial sector or high interest rates reflecting liquidity scarcity at the beginning of the crop season can limit area planted in a year. Uncertain crop prices at harvest time and input prices during the crop calendar can have severe impacts on farm income and become a social problem when affecting many farmers.